Effects of Post-Discharge Nutrition Tele-counselling on Cancer Patients with Chemotherapy - Hadiyati, Fauzatun; Efiyanna, Rina; Saman, Saman; Supriastuti, Ratna; Wardhiasih, Ertin; Delimunthe, Tiara Nurlita; Wijayanti, Dwi Nurmaya; Fuadiyah, Zuhrotul (Indonesian Journal of Cancer, 2025)
Background: Cancer patients often experience a decrease in dietary intake and body weight as a result of chemotherapy side effects. This can worsen the condition of cancer patients who are at risk of malnutrition or those who have previously been diagnosed with malnutrition while in the hospital. This study aimed to determine the effect of post-discharge nutrition tele-counseling on changes in dietary intake, body weight, and body mass index of cancer patients receiving chemotherapy.Method: This study was quasi-experimental with a pre-test and post-test control group design conducted on 86 subjects. Respondents who met the inclusion criteria consisted of those who were adult cancer patients (aged 18 years), undergoing chemotherapy in an inpatient setting with a 3-week cycle, able to consume food orally or via NGT, able to weigh and measure height, had the WhatsApp application on their cell phone, and can participate in the study for 3 weeks. The statistical analysis used an independent t-test for changes in energy, protein, and carbohydrate intake. The changes in fat intake, body weight, and body mass index (BMI) were used in the Mann-Whitney test.Results: There were significant effects of nutrition tele-counseling by WhatsApp on increasing energy intake (P = 0.001), protein (P = 0.006), fat (P = 0.026), and carbohydrate (P = 0.002) compared to the control group, which had a decrease in dietary intake. Body weight (P ≤ 0.001) and BMI (P = 0.001) had increased compared to the control group, which had a decrease.Conclusions: Post-discharge nutrition tele-counseling could increase dietary intake, body weight, and BMI for cancer patients undergoing a 3-week cycle of chemotherapy.